Transpacific Integration and Open Regionalism: The Case of Singapore as Associated State of the Pacific Alliance - Fonseca, Fabricio A.; Sanchez Orozco, Miriam L. (Nurimedia Co. Ltd., 2024)
The Transpacific integration process is entering its third decade, and it encompasses a vast number of economic agreements and a wide range of actors on both sides of the Pacific. In the side of Latin America, the Pacific Alliance (PA) and its member states have been identified as using the concept of open regionalism to maximize their integration efforts, not only between themselves, but also with their counterparts in the Asia-Pacific. With the introduction of the category of Associated State, the PA founding members (Chile, Colombia, Mexico and Peru) have been able to add a new dimension to this Transpacific integration process. In 2022, Singapore was the first country to receive that category after finalizing negotiations for a free trade agreement with all the Alliance members. Other candidates are Australia, Canada, New Zealand, and more recently, South Korea. This article intends to trace the process of Singapore’s partnership with the PA, exploring the different motivations and features of economic ties between both sides of this new development. Therefore, through the observation of qualitative data and descriptive statistics, we suggest that it is possible to move beyond material incentives and drives, and emphasize elements such as shared values and ideas, in order to better comprehend the decision of those actors in coming together and continue promoting notions associated with a liberal and multilateral trading system, as a preferred model for Transpacific cooperation. ©The authors ©Nurimedia Co. Ltd ©Korean Association Of International Studies
Introduction -- Open regionalism and the Pacific Alliance -- The PA and associated States -- The Pacific Alliance and Singapore -- Concluding remarks -- References.
Keywords: Interregionalism; Asia-Pacific; Latin America; International trade; FDI